REMEMBERING AND UNDERSTANDING GENOCIDE THROUGH THE ARTS: A CASE STUDY OF THE ARMENIAN GENOCIDE - Whitehorn, Alan (Armenian Folia Anglistika, 2024)
The article is dedicated to the 90th anniversary of the heroic novel The Forty Days of Musa Dagh. One of the most discussed and influential genocides globally is the Armenian Genocide which has been explored in journalistic, academic and artistic ways. Despite war-time censorship, the mass deportations and killings of the Armenians in the Ottoman Empire during World War One was covered extensively and graphically by the international press. Such atrocities became a catalyst for the emergence of the important analytic terms of ‘crimes against humanity’ and ‘genocide’, along with the extension of the concept of ‘war crimes’. These three terms constitute key conceptual aspects in international criminal law, history and the social sciences. In addition to new analytical frameworks seeking to portray the magnitude of mass atrocity crimes, we also have witnessed personal accounts within an Arts and Humanities format. The Arts have often explored the personal costs of war, genocide and their extended aftermath. Franz Werfel’s historical novel “The Forty Days of Musa Dagh” was an exemplary example and its international influence was extensive. Forms of coverage and commentary on genocide can include a range of approaches from journalistic accounts, academic historical writings, memoirs, museums, social science theorizing to various aspects of the Arts, such as novels, plays, poetry, film, paintings and music. While detached academic accounts are important to develop our analytical understanding; more engaged personal artistic forms of expression can be profoundly influential in fostering empathy and sympathy towards the victims. The Arts can be powerful forms of personal connection. In the tradition of Franz Werfel’s novel, an overview of a variety of works in the Arts about the Armenian Genocide will be discussed. Together, the different approaches of i) journalistic first-impressions, ii) the academic analytical mind and iii) the Arts’ passionate heart can help us to more effectively remember, understand, sympathize and educate about genocides. It is useful to employ a variety of ways of reaching potential bystanders to remember, understand and become more engaged to overcome the devastating impact of genocide.